2021
DOI: 10.3390/ijerph18189465
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Cancer Risks Associated with Nitrosamine Contamination in Commonly Used Medications

Abstract: Many nitrosamines are potent carcinogens, with more than 30 listed under California’s Proposition 65. Recently, nitrosamine contamination of commonly used drugs for treatment of hypertension, heartburn, and type 2 diabetes has prompted numerous Food and Drug Administration (FDA) recalls in the US. These contaminants include the carcinogens NDMA (N-nitrosodimethylamine) and NDEA (N-nitrosodiethylamine) and the animal tumorigen NMBA (N-nitroso-N-methyl-4-aminobutyric acid). NMBA and NDEA are metabolically and/or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…In fact, air, soil and water are supposed to contain NDMA and other related nitrosoamines, formed by interactions between secondary or tertiary amines with the oxidizing agents. A couple of studies point at the NDMA as a potent carcinogen (Li et al, 2021). Since Ranitidine also contains NDMA and increased angiogenesis is a prerequisite for the developing cancer, the present study was undertaken to assess the angiogenic potential of Ranitidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, air, soil and water are supposed to contain NDMA and other related nitrosoamines, formed by interactions between secondary or tertiary amines with the oxidizing agents. A couple of studies point at the NDMA as a potent carcinogen (Li et al, 2021). Since Ranitidine also contains NDMA and increased angiogenesis is a prerequisite for the developing cancer, the present study was undertaken to assess the angiogenic potential of Ranitidine.…”
Section: Discussionmentioning
confidence: 99%
“…However, the very low quantities of NDMA from food and water are easily ingested by human body without much medical issues. Exposure to persistently higher concentrations of NDMA, through drugs, may increase the risk of developing cancer (Li et al, 2021). Since 2019, the sell of Ranitidine is kept on hold by the FDA, USA due to its possible contamination with NDMA.…”
Section: International Journal Of Zoological Investigationsmentioning
confidence: 99%
“…For example, based on Li and others' research, NDMA induced lung tumors only in rat and mouse, whereas N‐nitrosodiethylamine (NDEA) induced tongue and oropharynx tumors only in hamster. The esophagus, liver, lung, and forestomach are targets of N‐nitrosamines (Li et al, 2021). Although it seems that humans are less susceptible to N‐nitrosamine carcinogenicity because of lower ROS generation rates and glutathione conservation and higher rate of O 6 ‐alkylguanine repair, there is risk of cancer caused by nitrosamines in food, water, and the environment (Lewis et al, 1997; Pegg, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…For example, based on Li and others' research, NDMA induced lung tumors only in rat and mouse, whereas N-nitrosodiethylamine (NDEA) induced tongue and oropharynx tumors only in hamster. The esophagus, liver, lung, and forestomach are targets of N-nitrosamines (Li et al, 2021).…”
mentioning
confidence: 99%
“…N-nitrosamine impurities are considered as a kind of potential human carcinogens [ 1 , 2 ]. Carcinogenicity experiments of 4-methylnitroamino-1, 3-pydinyl butanone and N-nitroso nornicotine in animals revealed that it could induce the tumors of lung, nasal cavity and liver in F344 rats, as well as the tumors of lung, trachea and nasal cavity in Syrian gold hamsters [ 3 ].…”
Section: Introductionmentioning
confidence: 99%